Case Study of Psychological Dynamics of Bipolar Affective Disorder Patients at Menur Hospital - Altu Nurta Rifdah; Nanda Audia Vrisaba (International Conference on Psychology and Education (ICPE), 2025)
This clinical case study investigates the psychological profile of a 20-year-old female patient diagnosed with Bipolar Affective Disorder at Menur Mental Hospital, Surabaya, Indonesia. The objective of this study is to examine the patient's emotional and behavioral patterns and explore contributing psychosocial factors. Data were collected through interviews, structured observations, and document analysis over a seven-day clinical internship. The patient experienced severe depressive episodes with psychotic features, emotional dysregulation, auditory hallucinations, suicidal ideation, and aggressive behavior. These symptoms were associated with unresolved trauma, familial instability, and lack of secure attachment figures. Analysis was conducted using Adler’s Individual Psychology framework, emphasizing inferiority feelings, maladaptive coping, and lack of social interest. The findings suggest that early trauma and inadequate support significantly impact the development and prognosis of bipolar disorder. This study highlights the importance of trauma-informed psychological interventions and contributes to the clinical understanding of mood disorders in young adults.